Severe combined immunodeficiencies: Expanding the mutation spectrum in Turkey and identification of 12 novel variants. (23rd March 2022) - Aykut, Ayca; Durmaz, Asude; Karaca, Neslihan; Gulez, Nesrin; Genel, Ferah; Celmeli, Fatih; Ozturk, Gulyuz; Atay, Didem; Aydogmus, Cigdem; Kiykim, Ayca; Aksu, Guzide; Kutukculer, Necil
Abstract: Human Inborn Errors of Immunity (IEIs) are clinically and genetically heterogeneous group of diseases, with relatively mild clinical course or severe types that can be life‐threatening. Severe combined immunodeficiency (SCID) is the most severe form of IEIs, which is caused by monogenic defects that impair the proliferation and function of T, B, and NK cells. According to the most recent report by the International Union of Immunological Societies (IUIS), SCID is caused by mutations in IL2RG, JAK3, FOXN1, CORO1A, PTPRC, CD3D, CD3E, CD247, ADA, AK2, NHEJ1, LIG4, PRKDC, DCLRE1C, RAG1 and RAG2 genes. The targeted next‐generation sequencing (TNGS) workflow based on Ion AmpliSeq™ Primary Immune Deficiency Research Panel was designed for sequencing 264 IEI‐related genes on Ion S5™ Sequencer. Herein, we present 21 disease‐causing variants (12 novel) which were identified in 22 patients in eight different SCID genes. Next‐generation sequencing allowed a rapid and an accurate diagnosis SCID patients.